International marketing - Czinkota, Michael R. (Dryden Press, 1998)
The book presents the basic concepts of international marketing; discusses the environmental forces that the international marketer has to consider; deals with the various activities necessary for international marketing planning and concentrates on the beginning of international marketing activities. The book also discusses strategy and marketing management issues most relevant to the expanded global operations of multinational corporations. Finally, the book addresses transitions in international marketing